Tell me who you are and I'll tell you what you deserve. The social construction of the subject of law of high- and low-class women based on the work of their lawyers - Hernández, Wilson (2023)
Judicial processes for alimony are commonly reduced to the economic, assuming that the constitution as a subject of law is automatic and independent of the extra-legal. In this article, we assume that this construction is affected by gender and class stereotypes. To analyze it, we focus on how lawyers socially construct the legal subject of lowand upper-class women claimants for alimony in Lima, Peru, based on analysis of judicial files and interviews with judges and prosecutors. In the work of lawyers, poor women are portrayed as resigned, blurring them as subjects of law. Although also resigned, upper-class women are resistant as they seek subsistence and quality of life with their pension. Beyond automatisms, being a subject of law is also a social construction that, fed by gender and class stereotypes, conflicts with its formal conception.